Ice worlds - Godfrey, Rachel; Pitts, Sorrel (UK Ladybird Books, 2018)
Lots of different animals live in the Arctic and the Antarctic. They must work hard to find food, and to look after their babies
Inspired by BBC Earth TV series and developed with input from BBC Earth natural history specialists
Science (Animals)
Keywords: Animals